Harmonic Generation Microscopy 2.0: New Tricks Empowering Intravital Imaging for Neuroscience - Lim, Hyungsik (Frontiers in Molecular Biosciences, 2019)
Optical harmonic generation, e.g., second- (SHG) and third-harmonic generation (THG), provides intrinsic contrasts for three-dimensional intravital microscopy. Contrary to two-photon excited fluorescence (TPEF), however, SHG and THG have found relatively specialized applications, such as imaging collagenous and non-specific tissues, respectively. Here we review recent advances to broaden the capacities especially for imaging the central nervous system. The fundamental contrast mechanisms are discussed as they encode novel information, including molecular origin, spectroscopy, functional probes, and image analysis, which lay foundations for promising future applications in neuroscience.